1993
DOI: 10.1002/art.1780360203
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecule expression in human synovial tissue

Abstract: Objective. We have previously shown that E‐selectin is expressed on endothelium in rheumatoid arthritis (RA) synovial tissues, and hence may be important in recruitment of leukocytes into the inflamed joint. In the present study, we determined whether other cellular adhesion molecules, including selectins and members of the integrin and immunoglobulin supergene families, are expressed in frozen synovium. Methods. We employed immunohistochemical staining to determine the distribution of CD31 (PECAM), CD44 (hyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
130
0
4

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(147 citation statements)
references
References 37 publications
(11 reference statements)
13
130
0
4
Order By: Relevance
“…The fibroblast-like synoviocytes (FLS) (3)(4)(5). These proteins are also expressed by fibroblasts in the sublining region.…”
Section: Type B Synoviocytes In the Intimal Liningmentioning
confidence: 99%
See 2 more Smart Citations
“…The fibroblast-like synoviocytes (FLS) (3)(4)(5). These proteins are also expressed by fibroblasts in the sublining region.…”
Section: Type B Synoviocytes In the Intimal Liningmentioning
confidence: 99%
“…Intercellular adhesion molecule 1 (ICAM-l), the hyaluronic acid receptor (CD44), PIintegrins (including the fibronectin and vascular cell adhesion molecule 1 [VCAM-I] receptors), and P3-integrins (such as the vitronectin receptor) are expressed by the RA intimal lining in amounts that are higher than those in normal tissue (3)(4)(5). These proteins are also expressed by fibroblasts in the sublining region.…”
Section: Type B Synoviocytes In the Intimal Liningmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the cells migrate through the endothelium engaging immunoglobulin superfamily members, predominately platelet-endothelial cell adhesion molecule-1 (PECAM-1/CD31) on leukocytes and endothelium (Butcher & Picker, 1996;von Andrian & Mackay, 2000). All these molecules are constitutively expressed and are upregulated in inflammation, except L-selectin, which is rapidly shed upon activation (Johnson et al, 1993;Schaible et al, 1994;Bennett et al, 1996;Issekutz TB et al, 1996;Mousa et al, 2000). Their blockade has been proposed as a novel anti-inflammatory strategy (Bogen et al, 1994;Issekutz AC et al, 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, immunohistochemical studies have demonstrated increased expression of VCAM-1 and ICAM-1 on RA synovial endothelial cells, although in contrast to E-selectin, staining was also detectable on other cell types, including synovial tissue macrophages, dendritic cells, fibroblasts, and some lymphocytes (4)(5)(6). Expression of these adhesion molecules is dramatically upregulated on a number of cell types, including endothelium, by proinflammatory cytokines such as tumor necrosis factor a (TNFa) and interleukin-1 (IL-1) (3), which we and others have demonstrated to play a central role in RA.…”
mentioning
confidence: 99%